Design of the solution-processed intermediate layer by engineering for inverted organic multi junction solar cells - Li, Ning; Stubhan, Tobias; Baran, Derya; Min, Jie; Wang, Haiqiao; Ameri, Tayebeh; Brabec, Christoph (Advanced Energy Materials, 2013)
An equivalent ohmic contact is successfully formed between low-conductivity poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)(PEDOT:PSS) and solution-processed aluminum-doped ZnO (AZO). Because of its promising optical and electrical properties, this combination can serve as an efficient interconnection layer as well as an optical spacer in inverted-structure organic tandem devices. © 2013 WILEY-VCH Verlag GmbH & Co.
Keywords: Aluminum-doped ZnO; Interconnection layers; Intermediate layers; Multi junction solar cells; Optical and electrical properties; Poly(3; 4-ethylenedioxythiophene):poly(styrenesulfonate); Solution-processed; Tandem devices Engineering controlled terms: Conducting polymers; Ohmic contacts; Zinc oxide Engineering main heading: Electric properties